Solar-wind street lighting -1 - Tan, Andrew Jia En. (2011)
The first section consists of introduction and the literature review of the project. This encompasses the purpose and objectives of this project. The literature review discuss why the project is carried out and the technology and methodology that are reviewed prior to this project. The literature review also gives a brief understanding of the subject.